PERAN KODE ETIK PROFESI DALAM MENINGKATKAN KUALITAS PELAYANAN TENAGA MEDIS DAN TENAGA KESEHATAN - Nazwa Rizqita Rahmadani; Nita Andinia Tri Pramesti (Jurnal Ilmiah Multidisiplin Ilmu, 2024)
The professional code of ethics has a crucial role in improving the quality of services provided by medical personnel and health workers. This research aims to explore the implementation of a professional code of ethics in the context of improving the quality of health services. The research method used is literature analysis to identify the role of professional ethical codes in health practice. The results of the analysis show that the professional code of ethics is not only a moral guideline, but also a basis for building ethical relationships between medical personnel, health workers and patients. Consistent application of a professional code of ethics can help increase public trust in the health profession and optimize the services provided. However, challenges in implementing and enforcing the code of ethics also need to be considered. This research provides a deeper understanding of the important role of professional codes of ethics in improving the quality of service for medical personnel and health workers, as well as providing a basis for further discussion in the context of ethical health practice.